PENGARUH TENAGA KERJA DAN BIAYA PRODUKSI TERHADAP PRODUKTIVITAS DAN PENDAPATAN INDUSTRI PENGRAJIN BATAKO DI KOTA DENPASAR - Satrya Devi, Anak Agung Ari; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
Globalization and free trade are challenges for Micro, Small and Medium Enterprises (MSMEs) to maintain their existence. One of them is related to the development of the brick making industry. This study aims 1) to analyze the effect of labor and production costs on the productivity of bricklay craftsmen in Denpasar City, 2) To analyze the influence of labor production costs and productivity on the income of bricklay craftsmen in Denpasar, 3)  to analyze the indirect effect of labor and production costs on the income of brick making craftsmen through productivity in the city of Denpasar. The population in this study were all business people in the brick making industry in the city of Denpasar. The sample was taken as a whole, amounting to 60 people craftsmen brick in the city of Denpasar. The analysis technique used in this study is path analysis. The results showed the labor and production costs have a positive and significant effect on the productivity of brick making craftsmen in the city of Denpasar. Labor, production costs and productivity affect the income of brick-making craftsmen in Denpasar City. There is an effect of labor and production costs on income through the productivity of brick-making craftsmen in Denpasar City. That is, when labor and production costs used can be used properly, it does not necessarily immediately increase the income of the brick-making craftsman without increasing productivity from the brick-making craftsman. Keywords: labor, production costs, productivity, income